Defect Detection on Printed Fabrics Via Gabor Filter and Regular Band (Journal of Fiber Bioengineering and Informatics, 2015)
Two methods are proposed in this paper to inspect printed fabrics. One method is to apply a genetic\ralgorithm to select parameters of optimal Gabor filter. Optimal Gabor filter can reduce the noise\rinformation of printed fabrics, which can achieve defect detection of printed fabrics. The other is in\rutilizing distance matching function to determine the unit of printed fabrics. Extracting features on a\rmoving unit of printed fabrics can realize defect segmentation of printed fabrics. Two approaches of\rdefect detection have their own advantages. Detecting method with Gabor filter using genetic algorithm\rhas perfect detection results of random printed fabrics, the other method based on statistical rule can\rreceive better defect detection results of regular printed fabrics. Both methods can be realized in practice\rand detection time of proposed methods can occupy little in total detection time.
Keywords: Defect Detection; Gabor Filter; Regular Band; Textile Fabrics